PERANAN KESULITAN EKONOMI, KEPUASAN KERJA DAN RELIGIUSITAS TERHADAP KESEJAHTERAAN PSIKOLOGIS - Hadjam, M Noor Rochman; Nasiruddin, Arif (Jurnal Psikologi, 2003)
This study examined the effects of economic pressure, job satisfaction and religiosity on psychological well being (PWB). 53 subjects (40 male, 13 female) rated themselves with 4 self rating scales. All subjects were married, and aged between 25-29 year (M=39.3 years). Regression analysis was used in this study. Results revealed that there is significant effect of three factors (economic pressure, job satisfaction, and religiosity) on PWB (Freg=3,987 p